Effectiveness of submucosal, oral, and intramuscular routes of dexamethasone administration in trismus, swelling, and pain reduction after the third lower molar surgery - Djordjević, Filip; Bubalo, Marija; Perić, Dejan; Mihailović, Djordje; Bukumirić, Zoran; Dubovina, Dejan (Vojnosanitetski pregled, 2023)
Background/Aim. Surgical extraction of impacted lower third molars is inevitably followed by the postoperative occurrence of trismus, swelling, and pain sensations to some degree. Corticosteroids (dexamethasone in particular) are commonly used drugs in the prevention of these complications. The aim of this study was to determine the effectiveness of dexamethasone in the prevention of postoperative complications, edema, trismus, and pain after the surgical extraction of impacted lower third molars, depending on the method of its administration. Methods. This prospective study involved 30 healthy patients, aged 18 years and above, of both sexes, with fully impacted lower third molar – class I or II and position B or C, according to Pell and Gregory classification system and vertical position according to Winter classification. All patients were divided randomly into three groups depending on the way of dexamethasone administration: oral – dexamethasone administered in the form of oral tablets in a dose of 4 mg one hour before the surgery; submucosal – dexamethasone solution administered submucosally in a dose of 4 mg in the area of the buccal sulcus, after the inferior alveolar nerve block anesthesia and additional anesthesia for the buccal nerve; intramuscular – dexamethasone solution administered intramuscularly in a dose of 4mg into the area of the deltoid muscle, right before the intervention. Preoperatively and at every follow-up (on the first, second, and seventh day postoperatively), interincisal distance, the degree of edema, and the level of pain with the use of a visual analog scale (VAS) were measured. On the seventh postoperative day, the total number of analgesics taken by the patients was recorded. Results. In the postoperative period, there was no statistically significant difference between the examined groups in terms of effectiveness in swelling, trismus, and pain reduction (p ˃ 0.05). Conclusion. There is no significant difference in dexamethasone effectiveness in postoperative trismus, swelling, and pain reduction after the third lower molar surgery, regarding the route of administration – oral, intramuscular, or local submucosal.